Stochastic income and conditional generosity - Christian Kellner; David Reinstein; Gerhard Riener (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
We study how other-regarding behavior extends to environments with uncertain income and conditional commitments. Should fundraisers ask a banker to donate "if he earns a bonus" or wait and ask after the bonus is known? Standard EU theory predicts these are equivalent; loss-aversion and signaling models both predict a larger commitment before the bonus is known; theories of affect predict the reverse. In field and lab experiments, we allow people to donate from lottery winnings, varying whether they decide before or after learning the lottery's outcome. Males are more generous when making conditional donations before knowing the outcome, while females' donations are unaffected. Males also commit more in treatments where income is certain but the donation's collection is uncertain. This supports a signaling explanation: it is cheaper to commit to donate before the uncertainty is unresolved, thus a larger donation is required to maintain a positive image. This has implications for experimental methodology, for fundraisers, and for our understanding of pro-social behavior.
Keywords: D64; C91; L30; D01; D84; 330; social preferences; contingent decision-making; signaling; uncertainty; prospect theory; affective state; gender; charitable giving; public goods; experiments; field experiments; bonuses